The Exterior Problem of Parabolic Hessian Quotient Equations - Huawei Zhao; Limei Dai (Mathematics, 2025)
In this paper, we investigate the exterior problem of parabolic Hessian quotient equations. By utilizing Perron’s method, we establish the existence of viscosity solutions that exhibit generalized asymptotic behavior at infinity. The main approach we adopt involves constructing sub- and supersolutions to handle the non-constant term on the right-hand side of the equation.